Correlation between saturated fatty acid intake and superoxide dismutase activities with telomere length in Minangkabau ethnic men - Minerva, Prima; Sulastri, Delmi; Lestari, Yuniar (International Journal of Research in Medical Sciences, 2019)
Background: Non-communicable diseases (NCD) are the leading cause of death globally today. In West Sumatra there has been an increase in NCD which exceeds the national average percentage. Telomere shortening is associated with occurrence of NCD. Shortening of telomeres is influenced by diet. The purpose of this study was to examine the relationship between Saturated Fatty Acid (SAFA) intake and Superoxide Dismutase (SOD) activity with the telomere length of Minangkabau ethnic men. Methods: This study was a cross sectional study. The sample of this study were 69 civil servants of Minangkabau male at district office in the Padang City, aged 40-50 years and according to the inclusion and exclusion criteria. Data on SAFA intake was obtained using Semi Quantitative Food Frequency Questionnaire (SQFFQ), SOD activity was measured using the Calorimetric method and telomere length was measured using Real Time Polymerase Chain Reaction (RT-PCR) by O’Challaghan and Fennech method. Data analysis was performed using Pearson correlation test with significance level p <0.05. Results: The results showed an average SAFA intake 10.47+3.46% calories, SOD activity 5.93+0.81units/ml and telomere length 468.94+199.25bp. Correlation test between telomere length with SAFA intake showed (p=0.338), and the correlation test between SOD activity and telomere length showed (p=0.01). Conclusions: From this study it was concluded that there was no correlation between SAFA intake and telomere length and there was a significant positive correlation between SOD activity and the telomere length of Minangkabau ethnic men.